Evaluation of Intercrops in Drip Irrigated Banana - Mohanty, S; Srivastava, R C; Behera, M S; Singandhupe, R B (Journal of Agricultural Engineering, 2006)
Longer gestation period of orchard crops is a major constraint towards crop diversification by small and marginal farmers. This constraint can be overcome by having an intercrop. In most of the cases, the intercrop is rainfed or surface irrigated which results in either poor yield or poor water use efficiency. Further the crop should be such which can be economically grown under the shade else the opportunity time of the crop should be short. Thus need was felt to select a crop which can grow under the shade as well as can be irrigated through existing drip system with slight modification. To fill this research gap, a study was undertaken on intercropping in banana orchard with two crops: turmeric and cowpea. The irrigation was applied by either micro tube or extension tube with dripper connected to existing lateral or in-line dripper connected to submain. The study indicated that turmeric irrigated by micro tube performed best. There was no adverse effect on hydrulics of total drip system by this modification to irrigate the intercrop. The growth and yield of banana was also not affected by the intercrops. The irrigation water use efficiency was highest in unirrigated intercrop treatments. The additional income from turmeric was about Rs. 23,700/- per ha/year which means that a good part of the investment in drip is recovered back within two years by intercrop alone.